Demography Integrated Surveillance for Health Assessment-Geriatric (DISHA-G), a rural cohort of older adults in Odisha, India - Jaya Singh Kshatri; Tanveer Rehman; Daisy J. A. Janssen; Susan D. Shenkin; Subrata Kumar Palo; Sanghamitra Pati (Discover Public Health)
Abstract With an increasing number of older people across low and middle income countries such as India, longitudinal observational research is required to understand the processes of aging, care seeking behaviours and outcomes in such groups. As most of the older adults in such regions live in rural areas with limited resources, and with no such cohorts available to carry out such studies, we have establied a first of its kind geriatric rural cohort in eastern India. This study describes the profile of a large cohort of 18,389 rural older adults, aged 50 years or more, that was built within a Health, Demography and Environment Surveillance System (HDESS). The study primarily focuses on profiling older adults’ sociodemographic and health characteristics, as well as their healthcare-seeking behavior patterns. We use exploratory regression analysis to understand factors influencing care-seeking preferences. We use R software packages for analysis and data management. The entire population of HDESS is 76,391 which has been establihed in 50 villages of Tigiria, Odisha state in eastern India, between 2021 and 2022. This cohort provides a valuable longitudinal platform for studying aging processes, chronic disease progression, and intervention implementation. Self-reported prevalence of chronic conditions and multimorbidity was 9.5%, with diabetes (10.6%) and hypertension (22.0%) the most common ones. Most rural older adults, irrespective of their wealth status, preferred public to private healthcare facilities (91%) for either mild illness, general care or emergency/severe illness. To reduce informal healthcare seeking behaviour (8.3%) of older adults in rural India, services need to be available, but social factors must also be addressed. The DISHA-G cohort provides a unique longitudinal platform to study aging and healthcare-seeking behaviors in rural India. Key findings reveal significant reliance on public healthcare and significant informal care-seeking, influenced by insurance coverage and socioeconomic status, highlighting barriers to formal care. Policy initiatives should focus on expanding health insurance coverage, improving accessibility to public healthcare, and addressing socioeconomic barriers to reduce reliance on informal care among rural older adults.